(untitled) (Homiletic, 2016)
Contrary to popular belief, what is known today as the prosperity gospel did not emerge ex nihilo in 1962 from the preaching of Kenneth E. Hagin. Long before Hagin began preaching his message that God wants Christians to be rich and experience good physical health, Protestant preachers of many different sects integrated their faith in Jesus Christ with their commitment to capitalism to justify theologically and to perpetuate socially the institution of African chattel slavery. This integration of theology and capitalism formed the first prosperity gospel of the New World: the slave prosperity gospel.